Exploring Students’ Reading Interest Through Tiktok Multimodal Literacy - Fakhrurrazi M. Amin (CV. Pusdikra Mitra Jaya, 2023)
This research aims to explore students' interest in reading by utilizing the TikTok application as a teaching tool for English. The study adopts a qualitative research design to gather data in the form of written or spoken expressions and observed behavior. Data collection methods include observation, interviews, and document analysis. The findings reveal that students exhibit a strong interest in using the TikTok application as a medium for reading. They perceive TikTok as a positive platform due to its multimodal nature, combining language with visual, auditory, and spoken elements in a comprehensive manner. Given its effectiveness in enhancing students' interest in reading, TikTok can be employed as a medium for teaching and learning reading in educational settings.